Urgensi Dakwah dan Problematika Masyarakat Global - Munawir Haris (LPPM IAIN Sorong, 2018)
Globalization influences all aspect of life, whether it is in social field, politic, economy, culture, education and in others field produced the kinds of influencing as positive and negative. There is an interesting development that writer finds in global society that the tendency of society has begun changing on quest of meaning life whether humanism and spiritual value. It relates with presenting of negative influencing of era globalization toward the society who forget the behavior as one of the part of eternity orientation. To answering that problem, Islam has given solution with the lesson in molded of Nashaihul ‘Ibad holy book translation. The writer chooses the product of Imam Nawawi al-Bantani because the holy book includes many materials in Islam guiding that are really interesting to be observed and the content can be contextualized to the global society.